Peran Stakeholder Dalam Pengembangan Desa Wisata Paksebali di Kecamatan Dawan, Kabupaten Klungkung, Bali - Semara, Sang Made Dwipa; Suryasih, Ida Ayu; Nugroho, Saptono (Peneliti.net, 2024)
Pasekbali Village is one of the tourist villages in Klungkung Regency in accordance with Decree No. 2/2017 on January 19, 2017. In developing tourism, Pasekbali Tourism Village requires the role of stakeholders consisting of the government, the private sector, and the community. The stakeholders have their respective roles and interests. These roles and interests will affect the cooperative relationship established in the management of Paksebali Tourism Village, in the form of a policy, similarity of vision and mission, main tasks and functions and other institutional rules. This research aims to find out the role of stakeholders in the development of Paksebali Tourism Village, and become a reference to develop the potential contained in Paksebali Tourism Village into a tourist attraction in order to improve the economy. The results of this research can be seen that Paksebali Tourism Village has natural, cultural, and artificial potential to be developed. And stakeholders play an important role in the development of the tourist village, especially the local government and local communities. Through the results of the analysis, it can also be seen that the strategies that can be carried out by stakeholders are divided into S-O strategies, S-W strategies, S-T strategies, and W-T strategies.